Odpowiedź :
Obliczenia od a) do c)
[tex](-5)-(-1\frac{3}{4})=(-5)+1\frac{3}{4}=-(5-1\frac{3}{4})=-(4\frac{4}{4}-1\frac{3}{4})=-3\frac{1}{4}\\\\(-2,2)+(-10\frac{1}{5})=-(2,2+10\frac{2}{10})=-(2,2+10,2)=-12,4\\\\(-1\frac{1}{3})+(-15)=-(1\frac{1}{3}+15)=-16\frac{1}{3}[/tex]
Obliczenia od d) do f)
[tex](-9)-(-4\frac{1}{4})=(-9)+4\frac{1}{4}=-(9-4\frac{1}{4})=-(8\frac{4}{4}-4\frac{1}{4})=-4\frac{3}{4}\\\\(-3\frac{2}{5})-4,8=-(3\frac{4}{10}+4,8)=-(3,4+4,8)=-8,2\\\\2\frac{1}{3}+(-5\frac{3}{5})=2\frac{1}{3}-5\frac{3}{5}=-(5\frac{3}{5}-2\frac{1}{3})=-(5\frac{9}{15}-2\frac{5}{15})=-3\frac{4}{15}[/tex]
Odpowiedź:
a) (-5) - (-1 i 3/4 = - 5 + 1 i 3/4= - 4 i 4/4 + 1 i 3/4= - 3 i 1/4
b) (-2,2 +( -10 i 1/5)= - 2 2 - 10,2 = - 12,4
c) ( - 1 i 1/3 ) + ( -15)= - 1 i 1/3 - 15 = - 16 i 1/3
d) (-9) - (-4 i 1/4)= -9 + 4 i 1/4= - 8 i 4/4 + 4 i 1/4= - 4 i 3/4
e) ( - 3 i 2/5) - 4,8= - 3,4 - 4, 8= -8,2
f) 2 i 1/3 + (-5 i 3/5)= 2 i 1/3- 5 i 3/5= 2 i 5/15 - 5 i 9/15= - 3 i 4/15
Szczegółowe wyjaśnienie: